Duality for a Class of Nondifferentiable Multiple Objective Programming Problems - Mond, B.; Husain, I.; Durga Prasad, M.V. (Journal of information & optimization sciences, 1988)
Mond-Weir and Wolfe type duals for a nondifferentiable multiple objective programming problem are formulated, and weak and strong duality theorems relating properly efficient solutions of the primal and dual problems are proved.